HYDRODYNAMICS AND SEDIMENT CHARACTERISTICS ON A BATHYMETRICALLY-CONTROLLED RIP CHANNEL IN PANGANDARAN BEACH - Hanif Santyabudhi Sutiyoso; Andi Egon (Bulletin of Geology, 2019)
Rip currents are hydrodynamic events that form vary alongshore depend on local setting of its bathymetry feature and forcing. When it occurs, it is important to understand the process in order to prepare safety issues on recreational beaches. Bathymerically-controlled rips are the focus in this study, as this type is commonly found on Indonesia’s coastal areas, particularly in south coast of West Java. This unique hydrodynamics feature affects sediment characteristic, particularly at the rip channel as the lower part (far from shore) tends to have coarser sediment due to larger friction. Such complex interactions need thorough investigation; therefore, a study was conducted in Pangandaran which well-known for its rip currents. Field observation was made to collect sediment sample on cross shore direction which shows finer sediment on upper rip channel and coarser sediment on the lower part with diameter size of 0.35 mm and 0.37 mm, respectively. In addition, simple simulations were also made to illustrate rip current movement on a channel. The result shows that in the strongest current area with over than 3.0 m/s current speed, i.e. on the lower part of rip channel, bed shear stress is found to be the strongest. It is been noticed as well that the bed shear stress forms a pattern which delineate overall movement of a rip current. Furthermore, the variation of bed shear stress is revealed as the main cause of sediment distribution along the cross-shore direction. Therefore, this simple approach qualitatively illustrates the dynamics of rip current phenomenon.